The Muppet Christmas carol [videorecording (Blu-Ray)] - Henson, Brian; Caine, Michael; Oz, Frank; Goelz, Dave; Whitmire, Steve, 1959-; Nelson, Jerry, 1934-2012; Williams, Paul, 1940-; Dickens, Charles, 1812-1870 (Disney Blu-ray., 2012)
The Muppets perform their version of the classic story of an old and bitter miser's redemption on Christmas Eve.